THE PATHOLOGIC DEPENDENCES OF MELANOMA GROWTH FROM COPPER HOMEOSTASIS - Клименко, А. О.; Струк, О. А.; Клименко, Ю. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The research of melanoma malignant growth nature, the perception of metabolic differences between normal and neoplastic cells are an important basis for appreciation of effective tumors treatment methods. It’s known, that malignant growth development is supported by not only local pathological alteration, but general reaction for tumor. That’s why the important moment in malignant growth discovery is research of some factors influenced for growth, development and differentiation of tissue cells. In this case, copper metabolism is very interesting, because this element is a part of many enzymes, has influence for cell’ separation, growth, tissue develop-ment, energetic metabolism in cells and immune reaction in human body. Due features and difficulties of diagnostics, high resistance of these pigment tumors for treatment, high potention to metastasis the problem of diagnostic and treatment of melanomas has big practical interest. Thus, the most important is study of pathogenesis mechanisms which can give us of possibility of modern treatment development and improve it efficacy.